Sweet Heritage: Preserving Meranaw Identity Through Mamis Delicacies - Minodar, Wedad U. Ramos; Bangcola, Hidaya B. (Future Science / FSH-PH Publications, 2025)
The purpose of the study is to help the Meranaw people to verify the veracity that behind their colorful, rich and beautiful culture, there is Mamis which symbolizes the royalty and hospitability of every Meranaw. In which every Meranaw occasions, engagements, merrymaking, and homecoming of people who had gone to Hajj, and during the two religious feasts, Eid’l Adha and Eid'l Fitr there should be a serving of sweet desserts together with the main course or dish. This study is anchored by various theories to strengthen the analysis. First is the Foodways Theory (Douglas, 1984) which analyzes food's role in shaping cultural identity and community, and the second one is the Culinary Cultural Heritage (Henderson, 2009) which highlights food's significance in preserv-ing cultural traditions. In determining the nature and the purpose of the study, the researchers used two ways of gathering data, Random Sampling method and Purposive Sampling method through the medium of self - made validated survey questionnaire and in – depth interview with the self-made guide questions. The study came up to conclude that the level of awareness among the respondents were on positive side result since majority of the re-spondents have tasted or seen these identified delicacies of the Meranaw despite the influences of the multi diversified colonial cuisine which indicates the preservation still remains today to some extent. Moreover, this study concludes that Mamis delicacy makes it more unique from other culture especially the ceremoni-als and rituals that are associated with it. These delicacies are commonly served during Meranao festivities in authentic Pagana. The method of preparation involved in making mamis has been transmitted from generation to generation which shape the char-acters and identity of Meranaws.